Measuring the patient safety culture at a tertiary care hospital in Pakistan using the Hospital Survey on Patient Safety Culture (HSOPSC). Issue 1 (16th March 2023) - Ahmed, Fasih Ali; Asif, Fozia; Munir, Tahir; Halim, Muhammad Sohail; Feroze Ali, Zehra; Belgaumi, Asim; Zafar, Hasnain; Latif, Asad
Abstract : Background: Patient safety is a top priority for many healthcare organisations worldwide. However, most of the initiatives aimed at the measurement and improvement of patient safety culture have been undertaken in developed countries. The purpose of this study was to measure the patient safety culture at a tertiary care hospital in Pakistan using the Hospital Survey on Patient Safety Culture (HSOPSC). Methods: The HSOPSC was used to measure the patient safety culture across 12 dimensions at Aga Khan University Hospital, Karachi. 2, 959 individuals, who had been working at the hospital, were administered the HSOPSC in paper form between June and September 2019. Results: The response rate of the survey was 50%. In the past 12 months, 979 respondents (33.1%) had submitted at least one event report. Results showed that the personnel viewed the patient safety culture at their hospital favourably. Overall, respondents scored highest in the following dimensions: 'feedback and communication on error' (91%), 'organisational learning and continuous improvement' (85%), 'teamwork within units' (83%), 'teamwork across units' (76%). The dimensions with the lowest positive per cent scores included 'staffing' (40%) and 'non-punitive response to error' (41%). Only the reliability of the 'handoffs and transitions', 'frequency of events reported', 'organisational learning' and 'teamwork within units' was higher than Cronbach's alpha of 0.7. Upon regression analysis of positive responses, physicians and nurses were found to have responded less favourably than the remaining professional groups for most dimensions. Conclusion: The measurement of safety culture is both feasible and informative in developing countries and could be broadly implemented to inform patient safety efforts. Current data suggest that it compares favourably with benchmarks from hospitals in the USA. Like the USA, high staff workload is a significant safety concern among staff. This study lays the foundation for further context-specific research on patient safety culture in developing countries.